Intolerance of Uncertainty and Eating Disorder Symptoms Over the Course of Intensive Treatment. Issue 3 (May 2021) - Reilly, Erin E.; Perry, Taylor R.; Brown, Tiffany A.; Wierenga, Christina E.; Kaye, Walter H.
Abstract: There is a critical need to identify processes that may influence outcome in existing treatments for eating disorders (EDs). Intolerance of uncertainty (IU), which refers to excessive distress regarding uncertain situations, is a well-established feature of anxiety disorders. Emerging work suggests that IU decreases over the course of cognitive-behavioral treatments and may relate to better treatment outcomes. As some literature has suggested IU may functionally maintain ED symptoms, testing whether changes in IU over treatment relate to outcome may result in the identification of novel treatment targets. This study aimed to build upon past work documenting links between IU and ED symptoms by exploring changes in IU over treatment and links between early change in IU (1-month) and discharge symptoms. Participants ( N = 274) receiving partial hospitalization treatment completed the Eating Pathology Symptoms Inventory and Intolerance of Uncertainty Scale at admission, 1-month post-admission, and discharge. Results suggested that IU significantly reduced from admission to discharge and that reductions in IU scores from admission to 1-month related to cognitive restraint, dietary restriction, and body image at discharge. However, this pattern did not hold for exercise, binge eating, or purging. Altogether, these results replicate past work supporting IU as a common feature across ED diagnoses and provide initial data suggesting that targeting IU early in treatment may enhance treatment outcomes. Highlights: Intolerance of uncertainty (IU) appears to be elevated in eating disorders (EDs). Participants with EDs completed measures of IU and ED symptoms throughout treatment. IU significantly decreased from intake to discharge. Early IU change related to lower discharge dietary restriction, restraint, and body image. IU change did not relate to exercise, binge eating, or purging at discharge.